Exploring the Nexus between Research and Development Expenditure and Economic Growth: Empirical Insights from Asian Countries - Dahal, Arjun Kumar; Bhattarai, Ganesh; Budhathoki, Prem Bahadur (NCC Journal, 2025)
This study examines the impact of R&D expenditure on economic growth in 35 Asian countries, analyzing 870 data points from World Bank reports and economic surveys. Guided by a positivist philosophy, it uses a quantitative, deductive, exploratory, and descriptive approach. Econometric tools, including panel unit root testing, Pedroni co-integration test, GMM, and Arellano-Bond test, reveal a long-term relationship between economic growth and past R&D spending. Economic growth increases by 1.5104 units for each unit rise in previous R&D expenditure, while past economic growth also positively influences current growth. However, a negative correlation exists between current R&D spending and growth, with a 2.844-unit decline per unit increase in spending, indicating inefficiencies or misallocation of R&D resources. The study highlights the need for policymakers to optimize R&D investments to enhance their effectiveness and ensure sustainable long-term economic development in Asian countries.